2021
DOI: 10.1029/2021wr030598
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Permeability of Partially Frozen Soil Using Floating Random Walks

Abstract: Fluid transport through porous granular media is important for understanding hydrate accumulation in marine sediments and frost heave in frozen soils. Take the hydrate-bearing sediment as an example: near the base of the hydrate stability zone, methane-rich pore fluid migrates upward and affects the growth of hydrates in the pore space of marine sediments (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The saturated vertical hydraulic conductivity has great explanatory power for the performance of all SMP schemes by controlling the liquid flux migration within soil layers, even though it is not a direct component of the SMP equations. As freezing progresses, the soil ice grows in the pores and narrows liquid flow paths, thus blocking water fluxes in frozen soils (Chen et al., 2021). Our study found that all four SMP schemes recommend a relatively low saturated vertical conductivity, reflecting the dwindling permeability of frozen soils (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The saturated vertical hydraulic conductivity has great explanatory power for the performance of all SMP schemes by controlling the liquid flux migration within soil layers, even though it is not a direct component of the SMP equations. As freezing progresses, the soil ice grows in the pores and narrows liquid flow paths, thus blocking water fluxes in frozen soils (Chen et al., 2021). Our study found that all four SMP schemes recommend a relatively low saturated vertical conductivity, reflecting the dwindling permeability of frozen soils (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive understanding of pore ice's role in controlling soil water migration and distribution is crucial for predicting hydrological and thermal dynamics, environmental changes, and climate feedbacks in areas affected by frozen ground. As a powerful tool for understanding the exchange of heat and water and their response to climate changes in permafrost regions (Blyth et al., 2021), land surface models (LSMs) have evolved to consider the impacts of soil ice, such as reduction in permeability (Azmatch et al., 2012; Chen et al., 2021; Watanabe & Osada, 2017), freezing point depression (Li et al., 2010), and changes in thermal properties (Kurylyk & Watanabe, 2013), to represent soil hydrological and thermal processes in permafrost regions more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in assessing groundwater runoff, which is often ignored (Hagen and Lafauconnier 1995;Killinqveit et al 2003), affect the credibility of water balance calculations. Field studies of rock permeability, necessary for the accurate determination of groundwater runoff, are carried out rarely (Quinton et al 2008;Kim et al 2020;Chen et al 2021). In Spitsbergen, this type of studies were completed only in the Ebba River catchment located in the Petunia Bay area, but mainly wellpermeable sediments were investigated (Marciniak et al 2011).…”
Section: Introductionmentioning
confidence: 99%